Hamiltonian energy in a modified Hindmarsh–Rose model - Zheng, Qianqian; Xu, Yong; Shen, Jianwei (Frontiers in Network Physiology, 2024)
This paper investigates the Hamiltonian energy of a modified HR(Hindmarsh-Rose) model to observe its effect on short-term memory. A Hamiltonian energy function and its variable function are given in the reduced system with a single node according to Helmholtz's theorem. We consider the role of the coupling strength and the links between neurons in the pattern formation to show the coupling and cooperative neurons are necessary for generating the fire or a clear short-term memory when all the neurons are in sync. Then, we consider the effect of the degree and external stimulus from other neurons on the emergence and disappearance of short-term memory, which illustrates that generating short-term memory will take a lot of energy, and the coupling strength could further reduce energy consumption. Finally, the dynamical mechanisms of the generation of short-term memory are concluded.